PENTINGNYA PENGAKOMODASIAN PENGALAMAN BELAJAR PADA PEMBELAJARAN IPA - Mega Wati (Jurnal Tunas Pendidikan, 2018)
Science learning includes three main elements that cannot be separated from one another, namely science as a product, process, and attitude. When the teaching and learning process, science learning must emphasize the aspects of the process (activity), namely about how students learn and the influence of the learning process for the development of the students themselves. Student learning activities can be built through accommodating direct learning experiences. Because learning experience is closely related to the development of process skills. Learning experience is a number of student activities carried out to obtain new information and competencies in accordance with the objectives to be achieved. Through accommodating learning experiences students can develop students' competencies in exploring and understanding nature scientifically. Accommodating learning experiences can be carried out by the teacher through several activities including (1) Expressing the learning goals that students must achieve before the learning activities begin. (2) Arrange learning tasks with students. (3) Provide information about learning activities that students must do. (4) Providing assistance and services to students who need it. (5) Providing motivation, encouraging students to learn, guide, etc. through the submission of questions. (6) Helping students to draw a conclusion. Through learning experience, teachers can improve the quality of learning so that it is more meaningful, and can develop all the potential that students have.